2006
DOI: 10.1289/ehp.7962
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Ultrafine Particles Alters Blood Leukocyte Expression of Adhesion Molecules in Humans

Abstract: Ultrafine particles (UFPs; aerodynamic diameter < 100 nm) may contribute to the respiratory and cardiovascular morbidity and mortality associated with particulate air pollution. We tested the hypothesis that inhalation of carbon UFPs has vascular effects in healthy and asthmatic subjects, detectable as alterations in blood leukocyte expression of adhesion molecules. Healthy subjects inhaled filtered air and freshly generated elemental carbon particles (count median diameter ~ 25 nm, geometric standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
5
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 53 publications
13
76
5
1
Order By: Relevance
“…TNF-a could not be detected in BALF. IL-1b showed a mild but not significant increase from 1 UFCP did not cause any detectable changes in airway inflammation [15]; however, they caused alterations in the expression pattern of adhesion molecules on blood cells, indicating increased retention of leukocytes in the pulmonary vascular bed [24]. The present study provides evidence that inhalation of elemental carbon particles at doses .40-fold above environmental relevant doses induces mild pro-inflammatory processes within 24 h of exposure.…”
Section: Secretion Of Osteopontin Into Balf After Inhalation Of Ufcpsmentioning
confidence: 48%
“…TNF-a could not be detected in BALF. IL-1b showed a mild but not significant increase from 1 UFCP did not cause any detectable changes in airway inflammation [15]; however, they caused alterations in the expression pattern of adhesion molecules on blood cells, indicating increased retention of leukocytes in the pulmonary vascular bed [24]. The present study provides evidence that inhalation of elemental carbon particles at doses .40-fold above environmental relevant doses induces mild pro-inflammatory processes within 24 h of exposure.…”
Section: Secretion Of Osteopontin Into Balf After Inhalation Of Ufcpsmentioning
confidence: 48%
“…Nanoparticles have enhanced capacity to produce reactive oxygen species, and, consequently, have widespread toxicity [18][19][20]. Consistent with these in vitro and in vivo reports, nanoparticle exposure also reportedly influences cardiopulmonary systems with or without predisposing diseases in human studies [21,22]. On the other hand, development of nanotechnology has increased the risk of types of particles other than combustion-derived particles in the environment, namely engineered nanomaterials [23].…”
Section: Introductionmentioning
confidence: 66%
“…390 Conversely, decreases in blood monocytes, basophils, eosinophils, and CD54 and CD18 adhesion molecule expression on monocytes after exposure to ultrafine carbon (10 to 50 g/m 3 ) among exercising asthmatic individuals and healthy adults have also been reported. 391 The authors suggested in the latter study that these results may represent the sequestration of these cells in tissue compartments such as the lung or vasculature, where there may be selective expression of the corresponding receptors for these ligands. 362 However, other recent human clinical studies have found no association between peripheral blood cell counts and exposure to fine PM or UFPs such as zinc oxide, 392 ultrafine carbon, 393 or diesel exhaust.…”
Section: Systemic Inflammationmentioning
confidence: 97%